Effective charges and ionicity in molten salts - Kavanoz, HB; Yilmaz, M; Gürbüz, H; Silbert, M (TAYLOR & FRANCIS LTD, 2002)
We have used experimental values of the entropies, near melting, of molten salts to calculate their effective charges by using a charge alpha spheres model in the Mean Spherical Approximation (MSA). We compare the values of the effective charges with the electronegativity differences for a number of 1:1 molten salts. We find a reasonable good correlation for the alkali halides, but no for the copper, silver and thallium halides, and we offer an explanation for these results.
Keywords: effective charge; ionicity; entropy; STATIC STRUCTURE; ALKALI-HALIDES; SIMULATIONS; POTENTIALS; TRANSPORT; LIQUID; MODEL; Chemistry; Physics